NMDA Receptors Coordinate Metabolic Reprogramming and Mitophagy in Schwann Cells to Promote Peripheral Nerve Regeneration - Fangzhen Shan; Xiaoying Yao; Qingqing Zhang; Ruolin Li; Lingmeng Kong; Qian Zheng; Nannan Zhang; Yuzhong Wang (Research)
Schwann cells (SCs) are indispensable for peripheral nerve regeneration, yet the mechanisms enabling their metabolic adaptation to meet the energetic demands of axonal repair remain elusive. Here, we identify N-methyl-D-aspartate (NMDA) receptors as central regulators of SC metabolic plasticity. In a mouse model of acute motor axonal neuropathy, nerve injury led to a marked decrease in NMDA receptor expression on SC. Functional studies revealed that NMDA receptors mediate calcium influx to drive glycolysis and oxidative phosphorylation via the phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin and hypoxia-inducible factor-1α/c-Myc pathways, ensuring adenosine triphosphate production for axonal repair. Simultaneously, NMDA receptors orchestrate ataxia telangiectasia-mutated and Rad3-related protein–autophagy related 13-dependent mitophagy to clear reactive oxygen species-damaged mitochondria, maintaining metabolic efficiency during energy stress. Targeted metabolomics, Seahorse flux, and molecular pathological analysis revealed NMDA receptor-dependent remodeling of glucose metabolism, tricarboxylic acid cycle, nucleotide synthesis, and mitochondrial ultrastructure in SC. NMDA receptor deficiency disrupts energy metabolism and impairs axonal survival following sciatic nerve injury, resulting in aggravated neurological deficits and hindered nerve regeneration. Crucially, NMDA receptor activation rescued axonal integrity and motor function in mice with acute motor axonal neuropathy, underscoring their therapeutic potential. Our findings establish NMDA receptors as dual regulators of SC energy metabolism and mitochondrial quality control, providing a novel strategy to enhance glia-axonal metabolic coupling in peripheral neuropathies.